PERANAN ORANG TUA DALAM KEBERHASILAN PENDIDIKAN AGAMA ISLAM DIMASA GLOBALISASI - Andamul Musyi Ridwanul Bari; Rano Sukmantara (CV. Lafadz Jaya, 2025)
Islamic Religious Education is fundamentally the responsibility of both parents, as stated in the Qur’an (QS. At-Tahrim: 6), and will be accounted for on the Day of Judgment. Parents are naturally endowed with deep affection for their children, who are their own flesh and blood. Consequently, they strive to protect, nurture, and guide their children to ensure they possess good religious understanding and noble character, becoming righteous offspring beneficial to their family, nation, and state. However, in the era of Globalization, which brings significant changes in various aspects including Islamic Education, parents sometimes neglect this responsibility. Whereas, a key factor in the success of Islamic Education is serious parental attention. Children, as the most valuable assets, risk falling into moral decadence and identity crises due to the currents of globalization. Since Islamic education cannot be entirely delegated to educational institutions, parents must play the most active and significant role. This article investigates why parents hold such a pivotal role in the success of Islamic education.